STUDENTS’ VOICES ON LECTURER’S SPEAKING TEACHING STRATEGIES AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Muhammad Ma’ruf Ramadhan H; Nurdevi Bte Abdul; Ratu Yulianti Natsir (English Language Teaching Methodology, 2021)
The objective of the research was to find out the students’ perception of teaching strategies and what kind of teaching strategies Lecturers used in English Speaking course at the third semester of English Department in Muhammadiyah University from three classes. The researcher used a descriptive quantitative research as design method because it was comparable to collect the data from students’ perception and gave questionnaire to collecting the data. The sample of this research was fifth semester grade students of English Department which consist of 47 students from three classes. The sample was taken by used Purposive Sampling Technique. Based on the findings, it was found that students gave positive perception on the lecturers teaching strategies used in teaching English speaking course and most of the lecturers used Active learning teaching strategies, the positive response came from their experience in learning process. The result of the research indicated that based on the likers score analysis there were 43 (91% ) out of the students was categorized positive perception in which score classification is 61-100 and 4 (9%) of the students were in neutral perception, and there were 166 students who say more often towards active learning strategies than other leading strategies It was categorized that lecturers’ teaching strategies used in teaching English speaking course effective to apply, it helps the learning teaching process in the class.